On singed product cordial of cone graph and its second power - S. Nada , A. Elrokh , Atef Abd El-hay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A graph is called singed cordial if it is possible to label the vertex by the function and label the edges by , where , so that and . In our work we present necessary and sufficient conditions for which cone graphs and their second power are singed product cordial